IoT-Based Real-Time Motorcycle Tracking and Security System Using RFID e-KTP Authentication and 4G LTE Cellular Connectivity - Faiza Cahya Ramadhani; Raka Pratindy (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This research addresses the rising problems of motorcycle theft and underage vehicle use by proposing an IoT-based security and tracking system with integrated access control and real-time monitoring capabilities. Methods – The study applied a Research and Development (R&D) methodology involving system design, hardware implementation, and performance evaluation. The prototype was developed using an ESP32-based Wemos D1 Mini 32, MFRC522 RFID module, RushFPV GNSS for positioning, and SIM7600 for 4G long-term evolution (LTE) communication. A self-hosted monitoring system was developed using PHP, MySQL, and Leaflet.js. The system was validated through multiple tests, including authentication accuracy, reading range, response time, GPS precision, and web functionality. Findings – The results show that the system achieved 100% authentication accuracy for registered e-KTP cards under the tested conditions, while rejecting the tested non-registered cards (e.g., SIM and ATM cards). Under the tested conditions, the effective RFID reading distance was limited to 0–2 cm. The system demonstrated a responsive performance with an average response time of 0.47 s. The GPS tracking results indicated low positional deviation based on the measurements. All the tested web-based monitoring features functioned as expected under the defined test scenarios. However, the evaluation was conducted at the prototype scale with limited testing scenarios. Research implications - Several limitations were identified, including the short RFID reading range, minor GPS inaccuracies, and dependence on a web-based interface. These factors may affect usability and limit the broader implementation in different environments. Originality – This study proposes an integrated system that combines 4G LTE connectivity, independent self-hosted monitoring, and RFID-based authentication using a government-issued e-KTP as a potential access control mechanism. The system demonstrates the feasibility of enhancing vehicle security and supporting controlled access, although further validation is required for real-world deployment.